Revitalization of museum collections through augmented reality to improve interactive educational services - Fortia Magfira; Marisha Pertiwi; Nolan Efranda; Feri Irawan; Rifaldi Herikson; Berta Erwin Slam; Sepli Yandri; Euis Ammelia; Basyaruddin Ismail (University of Merdeka Malang, 2026)
Museums play an important role in preserving cultural heritage; however, limited interactive media can reduce visitor engagement and understanding. The Sultan Sulaiman Badrul Alamsyah Museum faces a similar challenge, particularly the absence of digital visualization for exclusive collections that are rarely exhibited. This community service activity aims to revitalize museum collections through the use of digital technology and Augmented Reality (AR), while also strengthening the capacity of museum staff in delivering technology-based educational services. The implementation method included socialization, training, and mentoring on the use of an AR application for museum staff and students of SMAN 1 Tanjungpinang as educational users, involving a total of 25 participants. The evaluation was conducted descriptively through direct observation and simple questionnaires to assess user understanding, operational skills, and responses to the use of AR technology. The results show that eight exclusive museum collections were successfully digitized into 3D models and integrated into an Android-based AR application. After the intervention, museum staff demonstrated improved capability in operating and utilizing the AR application as an interactive educational medium. The application shows strong potential for sustainable use as part of museum services and for supporting educational activities and school visits.